A Universal Toughening and Energy‐Dissipating Strategy for Impact‐Resistant 3D‐Printed Composites - Xiang Hong; Peng Wang; Yu Ma; Weidong Yang; Junming Zhang; Zhongsen Zhang; Yan Li (Advanced Science)
Abstract 3D‐printed polymer‐based composites are promising for various engineering applications due to high strength‐to‐weight ratios and design flexibility. However, conventional matrix materials, such as polylactic acid and epoxy resin, often exhibit brittleness and limited impact resistance (< 10 kJ m−2). Herein, a universal strategy is reported for enhancing the ductility and impact energy absorption of 3D‐printed composites by leveraging the dynamic crosslinking of B─O dative bonds. To validate its effectiveness, a smart composite (PLA/SSG) comprising shear‐stiffening gel fillers embedded in a polylactic acid matrix is designed and its rate‐dependent mechanical adjustability along with 3D printability is evaluated. The resulting composite shows significant improvements in impact resistance, ductility, and strength‐ductility balance. Specifically, the multiple crack and localized plastic yielding of polylactic acid matrix induced by shear‐stiffening gel fillers enables PLA/SSG with a 40‐times increase in ductility; the “soft‐hard” phase transition of shear‐stiffening gel induced by B─O bonds endows PLA/SSG with a 330% improvement in impact energy absorption. This B─O bonds‐inspired strategy provides a universal approach for printing smart impact‐resistant composites and structures.